Extraction and characterization of humic acid from low-rank coal mined reserves in South Sumatra and its application on red chili (Capsicum annuum L.) in fertilizer exhausted soil - Hermawan, Mega Kartika; Sofyan, Emma Trinurani; Sudirja, Rija; Nurbaity, Anne (Brawijaya University, 2025)
Intensive use of inorganic fertilizers has led to soil degradation, decreased productivity, and increased greenhouse gas emissions. Humic acid (HA) offers a sustainable solution by improving soil health and nutrient uptake while reducing dependence on chemical inputs. However, commercial HA from leonardite is expensive and rarely available in Indonesia. This study aimed to develop a high-quality and cost-effective HA product from low-rank coal (LRC) mined in South Sumatra. Given LRC’s low calorific value and high organic content, it presents an underutilized but promising HA source. A descriptive quantitative approach was used, starting with LRC selection and modified extraction to obtain HA. Laboratory-scale characterization revealed that locally sourced HA shares many functional groups with commercial leonardite-based HA. Hydrofluoric acid pretreatment significantly increased HA yield from 26.3% to 44%. A field trial was conducted on degraded soil overused with inorganic fertilizers, using a completely randomized block design with five treatments and five replications. Red chili (Capsicum annuum L.) was selected because of its high economic value. Data were analyzed using ANOVA at a significance level of 5%. The results showed that the combination of HA derived from LRC with low phosphate fertilizer (150 kg ha-1 SP-36 + 27 kg ha-1 HA) significantly increased plant height, fruit yield, and soil P availability, resulting in a yield of more than 28 t ha-1. These findings demonstrate the potential of LRC as a sustainable HA source to restore degraded soils and increase crop productivity in Indonesia.